KONTRIBUSI SELF COMPASSION DAN STRES AKADEMIK TERHADAP PSYCHOLOGICAL WELL-BEING MAHASISWA SEMESTER AKHIR - Berliani, Novilia; Pratama, Mario (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Final semester students are vulnerable to experiencing a decline in psychological well-being due to the demands of completing their thesis and academic pressure. This study aims to determine the contribution of self-compassion and academic stress to psychological well-being in final semester students at Padang State University. The study used a quantitative method with a predictive design. The study subjects were 263 final semester students who were preparing their thesis, selected using a probability sampling technique with a proportionate cluster sampling method. Data were collected through an online questionnaire using adapted Psychological Well-Being (Ryff), Self-Compassion (Neff), and Perceived Academic Stress (Bedewy & Gabriel) scales. Data analysis was performed using multiple linear regression. The results showed that self-compassion and academic stress simultaneously had a significant effect on psychological well-being (F = 85.791; p = 0.000) with a coefficient of determination R² = 0.398, meaning that both variables explained 39.8% of the variation in psychological well-being. Partially, self-compassion had a significant effect (t = 8.375; p = 0.000) and academic stress also had a significant effect (t = 4.676; p = 0.000). The regression equation obtained was Y = 16.407 + 0.455X1 + 0.281X2. This finding confirms the importance of strengthening self-compassion and managing academic stress to support the psychological well-being of final semester students.